An approach to optimization of the choice of boiler steel grades as to a mixed-integer programming problem - Kler, Alexandr M.; Potanina, Yulia M. (Energy (Oxford), 2017)
One of the ways to enhance the energy efficiency of thermal power plants is to increase thermodynamic parameters of steam. A sufficient level of reliability and longevity can be provided by the application of advanced construction materials (in particular, high-alloy steel can be used to manufacture the most loaded heating surfaces of a boiler unit). A rational choice of technical and economic parameters of energy plants as the most complex technical systems should be made using the methods of mathematical modeling and optimization. The paper considers an original approach to an economically sound optimal choice of steel grade to manufacture heating surfaces for boiler units. A case study of optimization of the discrete-continuous parameters of an energy unit operating at ultra-supercritical steam parameters, in combination with construction of a variant selection tree is presented. •A case study on optimization of an ultra-supercritical power plant is demonstrated.•Optimization is based on the minimization of electricity price.•An approach is proposed to optimize the selection of boiler steel grades.•The approach is based on the construction of a variant tree.•The selection of steel grades for a boiler unit is shown.